Optimizing CFTR modulator therapy management for cystic fibrosis through the ReX platform - Yaacoby-Bianu, Karin; Cohen-Cymberknoh, Malena; Shoseyov, David; Lavi, Tal; Ostrovski, Ana; Shteinberg, Michal; Livnat, Galit (Frontiers in Pediatrics, 2023)
Cystic Fibrosis is a chronic multi-systemic disease that requires a daily treatment regimen. Therefore, there is sub-optimal adherence to CF therapies, and it was shown to impact its clinical and economic burden. Cystic fibrosis transmembrane conductance regulator modulators (CFTRm) are high cost medications that demonstrated benefit in clinical trials. The aim was to evaluate the safety, usability, and efficacy of the ReX platform in medication management of CFTRm for the treatment of people with CF (pwCF). ReX is a patient engagement platform consisting of a cloud-based management system and a cell-enabled handheld-device intended to dispense oral medication into the patient's mouth, following a pre-programmed treatment protocol. It provides real-time adherence data to caregivers and timely, personalized reminders to patients. This is a prospective multi-center open study for pwCF >12 years, who had been prescribed CFTRm [Elexacaftor/Tezacaftor/Ivacaftor (ETI) or Tezacaftor/Ivacaftor (TI)], and consent to use ReX platform to receive CFTRm and recorded their condition. Study was 12-24 months, with clinic visits where physical examination, Body Mass Index (BMI) and Pulmonary function test were performed, and user experience questionnaires were filled in. Ten pwCF from two CF Centers in Israel were included. The mean age was 31.5 years (range 15-74 years), eight were taking ETI, and two TI. No adverse events related to the use of the platform were reported. Median adherence to CFTRm in the first year was 97.5% (range 70-100%), and in the second year 94%(range 84-99%), which is higher than previous CFTRm adherence of ~80%.a remarkable improvement when compared to pre-ReX clinical assessment. No adverse events related to the use of the platform were reported.Patients reported ReX to be valuable to their treatment management and user friendly. Estimated mean FEV1% increased from 74.4% to 80.8% (p=0.004) over two years. Similarly, estimated BMI percentile increased from 53.5 to 59.0 (p<0.001). Using the ReX platform in medication management of pwCF treated by CFTRm is safe, easy to use and effective in improving the adherence to treatment and outcomes. Consequently, this device may potentially reduce costs to healthcare providers. Further larger studies are required to examine the benefits of the ReX platform.